2019
DOI: 10.1089/trgh.2018.0022
|View full text |Cite
|
Sign up to set email alerts
|

Motivators and Barriers to Accessing Sexual Health Care Services for Transgender/Genderqueer Individuals Assigned Female Sex at Birth

Abstract: Purpose: Individuals who were assigned female sex at birth (AFAB) but do not conform to the gender binary (i.e., transgender/genderqueer) often do not seek out necessary sexual health care, including Papanicolaou (Pap) tests, placing them at heightened risk of cervical cancer. Despite growing awareness, scant research has focused on the sexual health care experiences of this population in Midwestern and rural states. Methods: We used two approaches to develop a more detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 28 publications
1
50
0
2
Order By: Relevance
“…The qualitative results demonstrated that no single participant perceived themselves as "aware and well-informed" regarding HPV and cervical cancer, but quantitative survey results suggested high levels of knowledge and awareness regarding HPV (Harb et al, 2019). For instance, 100% of the participants were aware of facts about infection-that HPV could cause cervical cancer, that condoms did not prevent infection, that infection can be asymptomatic, and that routine CCS is necessary regardless of HPV vaccination status (Harb et al, 2019). But, survey questions regarding guidelines for CCS, (i.e., age for first screening and frequency for routine testing) were often answered incorrectly (Harb, et al, 2019).…”
Section: Tm's Perceptions Knowledge and Health Behaviors Toward Ccsmentioning
confidence: 90%
See 4 more Smart Citations
“…The qualitative results demonstrated that no single participant perceived themselves as "aware and well-informed" regarding HPV and cervical cancer, but quantitative survey results suggested high levels of knowledge and awareness regarding HPV (Harb et al, 2019). For instance, 100% of the participants were aware of facts about infection-that HPV could cause cervical cancer, that condoms did not prevent infection, that infection can be asymptomatic, and that routine CCS is necessary regardless of HPV vaccination status (Harb et al, 2019). But, survey questions regarding guidelines for CCS, (i.e., age for first screening and frequency for routine testing) were often answered incorrectly (Harb, et al, 2019).…”
Section: Tm's Perceptions Knowledge and Health Behaviors Toward Ccsmentioning
confidence: 90%
“…Interestingly, a mixed methods study identified contradictions in the knowledge levels of TM. The qualitative results demonstrated that no single participant perceived themselves as "aware and well-informed" regarding HPV and cervical cancer, but quantitative survey results suggested high levels of knowledge and awareness regarding HPV (Harb et al, 2019). For instance, 100% of the participants were aware of facts about infection-that HPV could cause cervical cancer, that condoms did not prevent infection, that infection can be asymptomatic, and that routine CCS is necessary regardless of HPV vaccination status (Harb et al, 2019).…”
Section: Tm's Perceptions Knowledge and Health Behaviors Toward Ccsmentioning
confidence: 93%
See 3 more Smart Citations